Automated designing of compartments of technical surfaces in educational process of designers - Vasilevskiy, O.; Makarenko, M. (Theory and practice of design, 2015)
Educational geometrical methods of automated designing of kinematic surfaces of the moldboards, realised in the form of computing programs that allow you to change the initial parameters of the pas, and explore the varied form of working surfaces of shelves, as well as getting in numerical or graphical form necessary to find solutions of variant information are considered.